2004
DOI: 10.1023/b:jots.0000014675.75686.ee
|View full text |Cite
|
Sign up to set email alerts
|

Attention, learning, and memory in posttraumatic stress disorder

Abstract: This study compared attention and declarative memory in a sample of combat veterans with posttraumatic stress disorder (PTSD, n = 24) previously reported to have reduced concentrations of the hippocampal neuronal marker N-acetyl aspartate (NAA), but similar hippocampal volume compared to veteran normal comparison participants (n = 23). Healthy, well-educated males with combatrelated PTSD without current depression or recent alcohol/drug abuse did not perform differently on tests of attention, learning, and mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
2
14

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 39 publications
4
68
2
14
Order By: Relevance
“…Since preclinical studies support the role for CA3 and CA1 hippocampal neurons in mediating eyeblink trace conditioning (Berger and Thompson, 1978;Clark and Squire, 1998;Moyer et al, 1990;Solomon et al, 1986;Weiss et al, 1996), the present data are similar to some studies demonstrating normal hippocampal-mediated neuropsychological function in PTSD (Neylan et al, 2004;Pederson et al, 2004;Vasterling et al, 1998).…”
Section: Discussionsupporting
confidence: 89%
“…Since preclinical studies support the role for CA3 and CA1 hippocampal neurons in mediating eyeblink trace conditioning (Berger and Thompson, 1978;Clark and Squire, 1998;Moyer et al, 1990;Solomon et al, 1986;Weiss et al, 1996), the present data are similar to some studies demonstrating normal hippocampal-mediated neuropsychological function in PTSD (Neylan et al, 2004;Pederson et al, 2004;Vasterling et al, 1998).…”
Section: Discussionsupporting
confidence: 89%
“…However, not all neuropsychological studies have noted memory impairments in PTSD; some studies have found no evidence of memory dysfunction related to PTSD (e.g., [57,60,61]) or any evidence that the group differences on the WAIS Vocabulary subtest could account for the group differences on the memory tests [62]. Possible explanations for this discrepancy include the following: (1) the neuropsychological studies associated with PTSD may be compromised by other psychotic or neurological disorders, substance abuse, and poor intelligence, and (2) a robust association between PTSD and verbal memory impairment perhaps reflects a motivational problem rather than a specific neuropsychological deficit [58].…”
Section: Discussionmentioning
confidence: 99%
“…Le but de cette recherche était de comparer des adolescents résidants en centre jeunesse qui présentent un ESPT à d'autres adolescents sur différentes variables reliées à cette problématique de santé mentale tels la dissociation, le stress physiologique et la (Bremner & Brett, 1997;Golier, Yehuda, Lupien, & Harvey, 2003;Golier et al, 2002;Koenen et al, 2001;Luecken, Dausch, Gulla, Hong, & Compas, 2004;Neylan et al, 2004;Nixon, Nishith, & Resick, 2004;Pederson et al, 2004;Rohleder, Joksimovic, Wolf, & Kirschbaum, 2004;Yehuda et al, 1995a;Yehuda et al, 1996). Seulement quelques études ont été effectuées auprès de jeunes (Eisen, Qin, Goodman, & Davis, 2002;Goenjian et al, 1996).…”
Section: Interprétation Des Résultatsunclassified
“…Ensuite, dans la formation des groupes, les recherches antérieures visaient une population ayant vécu le même type de traumatisme (Bremner & Brett, 1997;Eisen et al, 2002;Goenjian et al, 1996;Golier et al, 2003;Golier et al, 2002;Harvey, Naciti, Brand, & Stein, 2003;Luecken et al, 2004;Neylan et al, 2004;Nixon et al, 2004;Rohleder et al, 2004;Pederson et al, 2004;Stein, Kennedy, & Twamley, 2002;Yehuda et al, 1995c;Yehuda et al, 1996), alors que la présente recherche se base sur un ensemble de traumatismes différents les uns des autres (p. ex., chute grave, agression armée).…”
Section: Interprétation Des Résultatsunclassified
See 1 more Smart Citation